Interpretation of 1D Vector Controlled-Source Audio-Magnetotelluric (CSAMT) Data Using Full Solution Modeling - Imran Hilman Mohammad; Wahyu Srigutomo; Doddy Sutarno; Prihadi Sumintadiredja (Institute for Research and Community Services (LPPM) ITB, 2013)
In conventional controlled-source audio-magnetotelluric (CSAMT) prospecting, scalar CSAMT measurement is usually performed because of its simplicity and low operational cost. Since the structure of earth's conductivity is complex, the scalar CSAMT method can lead to a less accurate interpretation. The complex conditions need more sophisticated measurements, such as vector or tensor CSAMT, to interpret the data. This paper presents 1D vector CSAMT interpretation. A full solution 1D CSAMT forward modeling has been developed and used to interpret both vector and scalar CSAMT data. Occam's smoothness constrained inversion was used to test the vector and scalar CSAMT interpretations. The results indicate the importance of vector CSAMT to interpret CSAMT data in complex geological system.